THE INFLUENCE OF GREEN ACCOUNTING AND ENVIRONMENTAL PERFORMANCE ON SUSTAINABLE DEVELOPMENT GOALS - Novita Sari; Holiawati; Suripto (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine and analyze the influence of green accounting and environmental performance on the Sustainable Development Goals (SDGs), with gender diversity as a control variable. This research employs an associative quantitative approach using secondary data obtained from company annual reports. The population of this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022, totaling 227 companies. The sample was selected using the purposive sampling method, resulting in 46 companies observed over a period of four years, leading to 184 data observations. The data were analyzed using the panel data regression method, processed with EViews 12 software. The results indicate that green accounting and environmental performance have a significant influence on the achievement of SDGs. However, gender diversity does not show a significant impact on SDG attainment. These findings provide insight into the importance of implementing green accounting and enhancing environmental performance to support sustainable development goals.